Relation Between Crime and Moral Foundations of Social Order - Pavićević, Olivera; Bulatović, Aleksandra (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
The ratio of legality and legitimacy should have as its final outcome the enhancement of inclusiveness of social interactions as well as moral progress. The ambition of the authors was to illustrate in this paper certain aspects of the legality and legitimacy that have legal and theoretical broader social significance, as well as to highlight the most important aspects in which these insights disagree with the understanding of social reality in terms of moral foundations. In social practice, the weakening of the convergence of legality and legitimacy is manifested in different ways and is closely related to the phenomenon of crime and its political and social perception. The authors underlined some key issues that stand in the way of the process of decriminalization of Serbian society by perceiving it, both, as a lack of capacity to overcome the "friend–enemy" political concept in a broad social context, and, endurance in political manipulation of the crime phenomenon and the absence of a stable institutional balance. Starting from the understanding of the function of criminological theory also as a search for the answer to the question "what creates cruelty?" as the antipode to solidarity being 'the social glue', the authors provide arguments in support of concernes over raising moral cynicism and apathy as the predominant emotional feature of contemporary Serbian society by focusing its potential for transmutation into uncontrolled violence.